Road infrastructure qualitative changes in relation to traffic models and also to economic and location benefits of enterprises (Economic and Political Thought, 2022)
The article presents qualitative changes in road infrastructure in relation to traffic modeling and assessment of the impact of this infrastructure on the location of enterprises. The development of road infrastructure also affects measurable economic benefits achieved by enterprises in connection with motor transport of manufactured products in better conditions. This issue seems to be important and still valid because motor transport is still a very important field of economy. The article briefly presents the development of traffic models, as well as the phenomena of generated traffic and induced travel in the context of traffic modeling. In the face of dynamic qualitative changes in motor transport, they should be constantly monitored. Conducting this type of analysis is necessary both in an attempt to estimate the socio-economic effects of road infrastructure development, as well as in the context of the location decision of enterprises and their transport activity. Enterprises can obtain measurable benefits related to the use of traffic models in planning optimal transport activities and selection of the most effective markets for manufactured products.
Keywords: road infrastructure, motor transport, traffic modeling, enterprises, economic benefits